Heavy top quark mass in the minimal universal seesaw model - Panuluh Albertus Hariwangsa; Morozumi Takuya (EPJ Web of Conferences)
We study the hierarchy between MT , vL, and vR, the relevant energy scales of the Minimal Universal Seesaw Model (MUSM), where the two lightest quark families remain massless at tree level. We also predict the heavy top quark mass, mt′ . We do some numerical analysis using recent experimental data. Our numerical analysis demonstrates that MT is sensitive to the values of the Yukawa couplings. The heavy top quark mass (mt′ ) is predicted to be within the range from 1.4 TeV to 7.2 TeV for vR = 10 TeV.